Mechanistic Pathways of Malignancy in Breast Cancer Stem Cells - Yousefnia, Saghar; Seyed Forootan, Farzad; Seyed Forootan, Shiva; Nasr Esfahani, Mohammad Hossein; Gure, Ali Osmay; Ghaedi, Kamran (Frontiers in Oncology, 2020)
Breast cancer stem cells (BCSCs) are the minor population of breast cancer (BC) cells that exhibit several phenotypes such as migration, invasion, self-renewal, and chemotherapy as well as radiotherapy resistance. Recently, BCSCs have been more considerable due to their capacity for recurrence of tumors after treatment. Recognition of signaling pathways and molecular mechanisms involved in stemness phenotypes of BCSCs could be effective for discovering novel treatment strategies to target BCSCs. This review introduces BCSCs markers, their roles in stemness phenotypes, and the dysregulated signaling pathways involved in BCSCs such as MAP kinase, PI3K/Akt/ NFκB, TGF-β, Hedgehog (Hh), Notch, Wnt/β-catenin and Hippo pathway. Also, this review presents recent discovered molecular mechanisms implicated in chemotherapy and radiotherapy resistance, migration, metastasis and angiogenesis of BCSCs. Finally, we reviewed the role of miRNAs in BCSCs as well as several other therapeutic strategies such as herbal medicine, biological agents, anti-inflammatory drugs, monoclonal antibodies, nanoparticles and microRNAs which have been more considerable in the last decades.